High PM10 source regions and their influence on respiratory diseases in Canakkale, Turkey - AKKOYUNLU, BÜLENT OKTAY (SPRINGER, 2022)
This study investigates the impacts of high PM10 concentrations on respiratory diseases in Canakkale, Turkey. Daily mean high-PM10 values (> 100 mu g m(-3)) and daily total numbers of chronic obstructive pulmonary disease (COPD) and pneumonia patients are selected for different sexes and age groups (children, adults, and elderly) during the period 2007-2017. Mainly five different source regions of high-PM10 concentration levels are found as a result of implementation of Ward's minimum clustering technique to HYSPLIT 72-h backward trajectory. From 104 days, 19.2% are categorized as internal sources and are positively linked to COPD in female-adult and elderly patients at lag2 and lag3. The other sources are exhibited as external sources and originated from Europe, Sahara, Mediterranean, and Russia regions with the 34.6%, 22.1%, 13.5%, and 10.6% percentages of all episodes, respectively. During Europe-originated high-PM10 days, anthropogenic pollutants mainly cause an increase in the numbers of the elderly female (r = 0.55) and adult male pneumonia patients (r = 0.39) at lag5. Additionally, accompanied by the interaction between Genoa cyclone and surface high over Caspian Sea, natural dust particles are transferred from Sahara to Canakkale by strong southwesterly winds. As a consequence, obvious increases are shown in hospital admissions based on adult female COPD patients at lag1 (r = 0.50) and lag4 (r = 0.53). While Mediterranean origin particulate matter triggering the numbers of COPD and pneumonia-related diseases at lag2 and lag3, the region is exposed to more pneumonia diseases 2 days after arriving of Russia origin harmful pollutants.
Keywords: Respiratory diseases; PM10; Cluster analysis; Synoptic conditions; Turkey; OBSTRUCTIVE PULMONARY-DISEASE; AIR-POLLUTION; HOSPITAL ADMISSIONS; ATMOSPHERIC CIRCULATION; METEOROLOGICAL FACTORS; PARTICULATE MATTER; EUROPEAN CITIES; ISTANBUL; EXPOSURE; HEALTH